EVALUATION OF THE IMPLEMENTATION OF SCHOOL-BASED CURRICULUM IN IMPROVING THE LEARNING QUALITY OF PUBLIC JUNIOR HIGH SCHOOL NO. 2 IN BANYUASIN III OF BANYUASIN DISTRICT OF SOUTH SUMATRA PROVINCE - Bambang A. Loeneto (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2014)
Abstract: The study aims to evaluate the implementation of the School-Based Curriculum (SBC) in improving the quality of learning of the SMPN 2 Banyuasin III of Banyuasin District as well as identifying the factors which support and hamper the SBC implementation. Some identified problems concerning the SBC in the school were the unpreparedness ofthe schoolin the development of implementing SBC and some teachers did not really understand how to apply the SBC in their teaching and learning process in the classroom. It is a descriptive qualitative study looking at the concerned indicators of the Educational National Standard (ENS) stipulated by the Government Regulation No. 19 of 2005. The data were collected by interviewing some key informants. The results of the study show that in general the school has implemented the SBC as recommended by the ENS andcan also develop the curriculum based on its capacity. Yet, there are some teachers still lacking skills in preparing their lesson plans according to the school established syllabi and limited facility and infrastructure that could support the teaching and learning process in the school. It is recommended that the school find some alternative ways tosupport and facilitate the teaching and learning process such as having some financial aids from donors and the school committee. Key words: evaluation, SBC, curriculum, ENS (Educational National Standard)